Direct Comparison of Rat- and Human-Derived Ganglionic Eminence Tissue Grafts on Motor Function - Mariah J. Lelos (Cell Transplantation, 2016)
Huntington's disease (HD) is a debilitating, genetically inherited neurodegenerative disorder that results in early loss of medium spiny neurons from the striatum and subsequent degeneration of cortical and other subcortical brain regions. Behavioral changes manifest as a range of motor, cognitive, and neuropsychiatric impairments. It has been established that replacement of the degenerated medium spiny neurons with rat-derived fetal whole ganglionic eminence (rWGE) tissue can alleviate motor and cognitive deficits in preclinical rodent models of HD. However, clinical application of this cell replacement therapy requires the use of human-derived (hWGE), not rWGE, tissue. Despite this, little is currently known about the functional efficacy of hWGE. The aim of this study was to directly compare the ability of the gold standard rWGE grafts, against the clinically relevant hWGE grafts, on a range of behavioral tests of motor function. Lister hooded rats either remained as unoperated controls or received unilateral excitotoxic lesions of the lateral neostriatum. Subsets of lesioned rats then received transplants of either rWGE or hWGE primary fetal tissue into the lateral striatum. All rats were tested postlesion and postgraft on the following tests of motor function: staircase test, apomorphine-induced rotation, cylinder test, adjusting steps test, and vibrissae-evoked touch test. At 21 weeks postgraft, brain tissue was taken for histological analysis. The results revealed comparable improvements in apomorphine-induced rotational bias and the vibrissae test, despite larger graft volumes in the hWGE cohort. hWGE grafts, but not rWGE grafts, stabilized behavioral performance on the adjusting steps test. These results have implications for clinical application of cell replacement therapies, as well as providing a foundation for the development of stem cell-derived cell therapy products.